Trust based secure routing protocol using fuzzy logic in wireless sensor networks - Renubala, S.; Dhanalakshmi, K. S. (2014 IEEE International Conference on Computational Intelligence and Computing Research, 2014)
Wireless Sensor Networks (WSNs) are the ultimate field for applications including critical security actions like military surveillance and discovery of forest fire. Wireless sensor networks consider the multi-hop routing and it produces greatest security against identity deception through replaying routing information. The trust in the sensor network plays a essential role in the military and more applications. Secured data aggregation is a main standard that interests serious research work. Current trust-aware routing protocols use long-established cryptographic techniques, which are not proficient of well tackling the serious problem. The factors results in increased complexity, high overhead and poor link quality in case of a variety of cryptographic techniques. In this paper, a fuzzy logic based trust evaluation approach is proposed in order to obtain the secured routing. The proposed method uses the Bio-inspired Energy Efficient-Cluster (BEE-C) protocol and fuzzy logic to calculate the trust of the nodes. The proposed method finds the black hole and flooding attack and eliminates the attack. The trust values are compared with the threshold value. The trust values above the threshold are considered as trusted nodes and the packets are passed through the node. The trust value below the threshold value is termed as untrusted node and is eliminated. The proposed approach provides lesser overhead, packet loss, and delay with better packet delivery ratio than the existing game theory, Fuzzy with trust (LEACH).